Do hypoechoic endometrial cystic appearances before embryo transfer affect pregnancy rates in frozen-thawed cycles? - Ozge Karaosmanoglu; Nuri Peker; Burak Elmas; Aysen Yuceturk; Ilke Ozer Aslan; Omur Albayrak; Bulent Tiras (PLoS ONE, 2026)
Background The presence of hypoechoic cystic lesions (HCL) within the endometrium has been proposed as a potential factor influencing implantation and pregnancy outcomes during frozen–thawed embryo transfer (FET) cycles. However, evidence regarding their clinical significance remains limited and inconsistent. This study aimed to evaluate the effect of endometrial HCLs detected by transvaginal sonography on pregnancy and live-birth outcomes in women undergoing FET. Materials and Methods This retrospective study included 88 women undergoing hormone replacement therapy–FET cycles, divided into two groups: patients with HCLs ( n = 44) and controls with a normal trilaminar endometrial pattern ( n = 44). The primary outcome was the live birth rate (LBR), which represents the most clinically meaningful endpoint of treatment success. Secondary outcomes included the clinical pregnancy rate (CPR) and miscarriage rate, while HCL size was analyzed as a secondary exploratory variable to assess potential associations with IVF outcomes. Results There were no significant differences between groups in age, body mass index, duration of infertility, or endometrial thickness. The groups were also comparable regarding infertility cause, embryo-transfer day, and number of embryos transferred. The LBR, the primary outcome, was 52.3% in the HCL group and 50.0% in controls ( p = 0.670; OR = 1.10, 95% CI 0.47–2.53). Clinical pregnancy occurred in 68.2% of patients in both groups ( p = 1.000), and biochemical pregnancy in 4.5% vs 2.3% ( p = 1.000). Miscarriage rates were 20.5% and 15.9%, respectively ( p = 1.000). No significant association was found between HCL size and any reproductive outcome. Conclusion Hypoechoic cystic lesions within the endometrium do not appear to adversely affect pregnancy or live-birth outcomes in FET cycles when adequate endometrial thickness (≥7 mm) and a trilaminar pattern are present.